Heart rate variability response to mental arithmetic stress is abnormal in first-degree relatives of individuals with schizophrenia - Castro, Mariana Nair (2009)
Background: Schizophrenia patients exhibit an abnormal autonomic response to mental stress. We sought to determine the cardiac autonomic response to mental arithmetic stress in their unaffected first-degree relatives. Methods: Heart rate variability (HRV) analysis was performed on recordings obtained before, during, and after a standard mental arithmetic task to induce mental stress. 22 unaffected first-degree relatives of patients meeting DSM-IV criteria for schizophrenia (R) and 22 healthy individuals (C) were included in this study. Results: Patients' relatives (R) had a normal response to the mental arithmetic stress test, showing an increased heart rate compared with controls. They also displayed the characteristic pattern of relative contributions of HRV components that consists of increased low-frequency (LF) HRV and decreased high-frequency (HF) HRV. Recovery of the resting pattern of HRV immediately after stress termination was observed in healthy subjects (LF 62 ± 16% vs. 74 ± 10%, HF 37 ± 16% vs. 25 ± 10%, F = 9.616, p = 0.004), but not in patients' relatives (LF 60 ± 19% vs. 70 ± 13%, HF 40 ± 19% vs. 29 ± 13%, F = 8.4, p = 0.056). Conclusions: First-degree relatives of schizophrenia patients exhibit an abnormal pattern of protracted response to mental arithmetic stress, though less intense than that observed in patients in a previous study. This suggests that a pattern of autonomic response to stress may therefore be familial and heritable.